Virus versus host plant microRNAs: who determines the outcome of the interaction? - Fatemeh Maghuly; Rose C Ramkat; Margit Laimer (PLoS ONE)
Considering the importance of microRNAs (miRNAs) in the regulation of essential processes in plant pathogen interactions, it is not surprising that, while plant miRNA sequences counteract viral attack via antiviral RNA silencing, viruses in turn have developed antihost defense mechanisms blocking these RNA silencing pathways and establish a counter-defense. In the current study, computational and stem-loop Reverse Transcription - Polymerase Chain Reaction (RT-PCR) approaches were employed to a) predict and validate virus encoded mature miRNAs (miRs) in 39 DNA-A sequences of the bipartite genomes of African cassava mosaic virus (ACMV) and East African cassava mosaic virus-Uganda (EACMV-UG) isolates, b) determine whether virus encoded miRs/miRs* generated from the 5'/3' harpin arms have the capacity to bind to genomic sequences of the host plants Jatropha or cassava and c) investigate whether plant encoded miR/miR* sequences have the potential to bind to the viral genomes. Different viral pre-miRNA hairpin sequences and viral miR/miR* length variants occurring as isomiRs were predicted in both viruses. These miRNAs were located in three Open Reading Frames (ORFs) and in the Intergenic Region (IR). Moreover, various target genes for miRNAs from both viruses were predicted and annotated in the host plant genomes indicating that they are involved in biotic response, metabolic pathways and transcription factors. Plant miRs/miRs* from conserved and highly expressed families were identified, which were shown to have potential targets in the genome of both begomoviruses, representing potential plant miRNAs mediating antiviral defense. This is the first assessment of predicted viral miRs/miRs* of ACMV and EACMV-UG and host plant miRNAs, providing a reference point for miRNA identification in pathogens and their hosts. These findings will improve the understanding of host- pathogen interaction pathways and the function of viral miRNAs in Euphorbiaceous crop plants.